2016
DOI: 10.4067/s0717-97072016000400006
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Arsenic and Mercury in the Aquatic Ecosystem of the Five Chilean Reservoirs

Abstract: Arsenic and mercury are among the metals and metalloids more toxic to the ecosystem. A quantification method by atomic absorption spectroscopy with hydride generator (AAS-HG) to determine total As and cold steam to determine Hg was optimized and validated in various matrices: superficial water, interstitial or pore water, sediments and in gill, liver and muscle of two fish species, a silverside (Basilichthys microlepidotus) and a catfish (Trichomycterus areolatus). The quality of the results was tested using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Both species inhabited the Camisas River, but after the construction of the Corrales Dam populations were separated upstream and downstream from the dam. Several years after the Corrales Dam was built, physicochemical analysis showed differences in total phosphorus, iron, copper, and manganese between upstream and downstream sections of the river (Copaja, Muñoz, et al, 2016), and fish showed higher mercury accumulation upstream compared with downstream from the dam (Copaja, Nuñez, & Veliz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Both species inhabited the Camisas River, but after the construction of the Corrales Dam populations were separated upstream and downstream from the dam. Several years after the Corrales Dam was built, physicochemical analysis showed differences in total phosphorus, iron, copper, and manganese between upstream and downstream sections of the river (Copaja, Muñoz, et al, 2016), and fish showed higher mercury accumulation upstream compared with downstream from the dam (Copaja, Nuñez, & Veliz, 2016).…”
Section: Introductionmentioning
confidence: 99%